Integration of Ultrananocrystalline Diamond (UNCD)-Coatings on Chemical-Mechanical Surface Nano-structured (CMNS) Titanium-Based Dental Implants. (2020) - Sur, Debashish; Tirado, Pablo; Alcantar, Jesus; Auciello, Orlando; Basim, G. Bahar
Abstract: This paper focuses on describing the integration of ultrananocrystalline diamond (UNCD) coating on pure titanium-based dental implants (DIs) integrated with the surface pre-treatment by chemical-mechanical nano-structuring (CMNS) process. The combination of the UNCD coating with the CMNS metal surface treatment provides a transformational process to produce a new generation of metallic implants. CMNS promotes a uniform and dense titanium oxide interface and UNCD enables higher resistance to chemical-induced corrosion by oral fluids and enhanced bone attachment due to superior bone cell growth on C atoms (element of life in human DNA and cell). The main focus of the presented research is to establish the preliminary studies on the integration of the UNCD coating process on CMNS treated dental implants to promote corrosion resistance and biocompatibility. It is demonstrated that the CMNS process in the presence of an oxidizer (1M to be optimal) induces a tailored interface to promote UNCD coating capability through effective interface passivation leading to uniform surface coverage. The final implant product is observed to have improved corrosion potential and enhanced hydrophobicity indicating better biocompatibility providing the basis for a new generation of superior DIs. The findings can further be extended to the hip, knee, and other orthopedic metallic implants, which require major performance improvements, particularly in reducing or eliminating in-vivo body fluid-induced chemical corrosion.